Sarsasapogenin ameliorates diabetes‐associated memory impairment and neuroinflammation through down‐regulation of PAR‐1 receptor - Kong, Li; Liu, Yue; Zhang, Yu‐Meng; Li, Yu; Gou, Ling‐Shan; Ma, Teng‐Fei; Liu, Yao‐Wu (Phytotherapy research, 2021)
Sarsasapogenin (Sar), a natural steroidal compound, shows neuroprotection, cognition‐enhancement, antiinflammation, antithrombosis effects, and so on. However, whether Sar has ameliorative effects on diabetes‐associated cognitive impairment remains unknown. In this study, we found that Sar ameliorated diabetes‐associated memory impairment in streptozotocin‐induced diabetic rats, evidenced by increased numbers of crossing platform and percentage of time spent in the target quadrant in Morris water maze tests, and suppressed the nucleotide‐binding domain and leucine‐rich repeat containing protein 1 (NLRP1) inflammasome in hippocampus and cerebral cortex. Furthermore, Sar inhibited advanced glycation end‐products and its receptor (AGEs/RAGE) axis and suppressed up‐regulation of thrombin receptor protease‐activated receptor 1 (PAR‐1) in cerebral cortex. On the other hand, Sar mitigated high glucose‐induced neuronal damages, NLRP1 inflammasome activation, and PAR‐1 up‐regulation in high glucose‐cultured SH‐SY5Y cells, but did not affect thrombin activity. Moreover, the effects of Sar were similar to those of a selective PAR‐1 antagonist vorapaxar. Further studies indicated that activation of the NLRP1 inflammasome and NF‐κB mediated the effect of PAR‐1 up‐regulation in high glucose condition by using PAR‐1 knockdown assay. In summary, this study demonstrated that Sar prevented memory impairment caused by diabetes, which was achieved through suppressing neuroinflammation from activated NLRP1 inflammasome and NF‐κB regulated by cerebral PAR‐1. Highlights Sarsasapogenin ameliorated memory impairment caused by diabetes in rats. Sarsasapogenin mitigated neuronal damages and neuroinflammation by down‐regulating cerebral PAR‐1. The NLRP1 inflammasome and NF‐κB signaling mediated the pro‐inflammatory effects of PAR‐1. Sarsasapogenin was a pleiotropic neuroprotective agent and memory enhancer in diabetic rodents.